Antecedents of borrower participation in tourism micro enterprises moderated by a microfinance institution in Semporna, Sabah, Malaysia - Ibrahim, Mohd Romzee (2019)
The tourism industry is seen as a sector that can provide significant opportunities to local communities through the establishment of tourism enterprises. In most situations, these tourism enterprises will be in the form of micro businesses established and operated by the local community. The research in this field highlights the lack of participation in tourism micro enterprises among local communities as self-employed local communities instead tend to operate their own businesses in order to survive day-to-day without having any formal education and entrepreneurial skills. Therefore, this study aims to evaluate the indicators that are attributed to community participation and examining the factors contributing to the community’s motivation to participate in tourism micro enterprises. Amanah Ikhtiar Malaysia (AIM) is the moderating element in this regard helping to improve and influence its borrowers to engage in tourism-related enterprises. A structured face-to-face survey was conducted to evaluate the participation of borrowers’ in tourism micro enterprises in Semporna, Sabah which involved a total of 389 borrowers using a multi-stage random sampling method. Stepwise and Hierarchical regression model were utilised through exploratory factor analysis (EFA) to examine the conceptual research model developed in this study with and without the AIM’s role in the relationship between the participation indicator, and its interaction effect. The findings of this study indicate that motivation of the local community to participate was influenced by their ability to manage the enterprise, the value chain, and support by the institution, income generated from the business and the adaptability to manage critical issues surrounding the study location. AIM contributed towards moderating the influence by enhancing the effect of borrowers’ participation in the tourism micro enterprise. It was found that the capability of borrowers’ was the most significant factor contributing to their involvement. It can, therefore, be concluded that participation does not occur through memberships although the authority which is the power holder needs to exercise their role in encouraging participation through evaluating local community characteristics regarding their capabilities towards fulfilling community expectations. Accordingly, a microfinance institution (AIM) is recommended to equip borrowers with appropriate knowledge, training and entrepreneurial skills to take advantage of the opportunities brought about through tourism in Semporna. Also, integration with various stakeholders such as local authorities at the federal and state government levels, non-governmental agencies and the private sector is essential in its delivery system to facilitate the creation of sustainable entrepreneurial activities especially towards the establishment of tourism micro enterprises.